: одобрен конференцией рабочих и служащих (1985)
Приложения: с. 12-73, [1] Титульного листа нет, описание составлено по обложке Экземпляры: УКП (20201030) / Инвентарный номер: АП19850157 / Сис.шифр: 67.405 / Авт.знак: К 60 / ГРНТИ: 14 / ББК: 67.405.100